2017
DOI: 10.1101/gr.219675.116
|View full text |Cite
|
Sign up to set email alerts
|

Extending the spectrum of DNA sequences retrieved from ancient bones and teeth

Abstract: The number of DNA fragments surviving in ancient bones and teeth is known to decrease with fragment length. Recent genetic analyses of Middle Pleistocene remains have shown that the recovery of extremely short fragments can prove critical for successful retrieval of sequence information from particularly degraded ancient biological material. Current sample preparation techniques, however, are not optimized to recover DNA sequences from fragments shorter than ∼35 base pairs (bp). Here, we show that much shorter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
90
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 47 publications
1
90
0
Order By: Relevance
“…Other studies conducted with tooth and bone tissue also found no significant differences in average DNA fragment lengths recovered after modifying extraction procedures with extended digestion steps or bleach-based decontamination washes (Damgaard et al, 2015;Gamba et al, 2016;Korlevic et al, 2015). But a more recent report by Glocke and Meyer (2017) found that EDTA interferes with recovery of short DNA fragments. In general, reports comparing aDNA extraction methods have suggested that digestion time may be a strong influence on recovery rates and characteristics of endogenous aDNA.…”
Section: Discussionmentioning
confidence: 93%
“…Other studies conducted with tooth and bone tissue also found no significant differences in average DNA fragment lengths recovered after modifying extraction procedures with extended digestion steps or bleach-based decontamination washes (Damgaard et al, 2015;Gamba et al, 2016;Korlevic et al, 2015). But a more recent report by Glocke and Meyer (2017) found that EDTA interferes with recovery of short DNA fragments. In general, reports comparing aDNA extraction methods have suggested that digestion time may be a strong influence on recovery rates and characteristics of endogenous aDNA.…”
Section: Discussionmentioning
confidence: 93%
“…(Meyer et al, 2012) The single-strand approach has shown higher efficiency in the recovery of degraded and shorter DNA fragments. (Gansauge et al, 2017; Glocke & Meyer, 2017) Several recent studies have also shown that single-strand library preparation improved the recovery of cfDNA from cancer patients,(Snyder et al, 2016) transplantation recipients(Burnham et al, 2016) and maternal plasma. (Vong et al, 2017) It is of great significance to determine whether single-strand library preparation could indeed improve the performance of cfDNA analysis in clinical practice, especially in early-stage cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Sample pretreatment may also be unpredictable (Basler et al, 2017) and has even been contra-indicated for samples with very limited availability of bone material (Korlevi c et al, 2015). A third approach for increasing endogenous content is to utilize laboratory methods that target specific DNA fragment sizes, as reported for DNA extraction (Dabney et al, 2013;Glocke & Meyer, 2017) and some library preparation methods (Bennett et al, 2014). These increases presumably reflect substantial differences in the fragment length distributions of endogenous and contaminant DNA.…”
mentioning
confidence: 99%